Two-dimensional black phosphorus for rechargeable batteries - Zhang, Yu (2018)
The increasing demand of clean and sustainable energy drives the development of energy storage devices. Rechargeable batteries, including lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs), have been considered as one of the most promising energy storage systems. However, it is still desirable to develop LIBs and SIBs with high energy storage, fast rate capability and long stability to meet their potential applications in portable electronic devices, electric vehicles (EVs) and hybrid electric vehicles (HEVs). Phosphorene, mono- or few-layer black phosphorus (BP), has attracted much attention as a promising anode for rechargeable batteries, due to its high theoretical specific capacity (2596 mAh g-1) and ultrafast Li/Na ions diffusion along the zigzag direction. However, it faces major challenges of low-yield preparation of phosphorene and the poor air-stability. In addition, phosphorene exhibits low initial reversible capacities and fast capacity fading when tested as anodes for LIBs and SIBs, due to the sluggish reaction kinetics and large volume change (-300%). Therefore, large-scale preparation methods, effective passivation approaches and advanced strategies towards improved electrochemical performance are necessary before the direct application of phosphorene into these areas. In our studies, we aim to address the problems aforementioned. Firstly, we identify formamide as an appropriate solvent to produce high-yield phosphorene with good crystallinity and tunable size distributions via liquid-phase sonication of bulk BP, which largely outperforms the commonly used ones (e.g., NMP, DMF, IPA) in previous reports. In addition, phosphorene obtained in formamide can be stable for further processing and applications. Furthermore, a densely-packed graphene-phosphorene composite (PG-SPS) is designed and prepared via a facile spark plasma sintering (SPS) method, during which densification and reduction process take place simultaneously. As a result, the PG-SPS sample exhibits much improved air-stability due to effectively suppressing the permeation of water or oxygen molecules into the sample. Importantly, the densely packed PG-SPS sample shows improved volumetric capacities due to its high packing density (0.6 g cm-3) without scarifying its electrochemical performance. In addition, to enhance the charge transfer kinetics and surface wettability with electrolyte, nanoscale surface engineering of exfoliated few-layer BP is performed by homogeneous deposition of horizontally aligned PEDOT nanofibers on surface-modified BP nanosheets. The as-obtained BP/PEDOT composites exhibit much improved wettability towards the electrolyte compared to that of the pure BP nanosheets. Accordingly, the purposely engineered E-BP/PEDOT architecture exhibits significantly enhanced reversible specific capacities compared to that of the pure few-layer BP electrode. Importantly, due to the high mass percentage of the BP in the sample, the Na storage properties of E-BP/PEDOT outperform that of the E-BP/graphene composites based on the overall mass of whole electrodes. Furthermore, a OD-2D heterostructure of Ni2P nanocrystals (NCs)-BP nanosheets (denoted as NhP@BP) was also constructed via a facile strategy. In such a heterostructure, the 2D morphology of BP nanosheets is well maintained and Ni2P NCs display an average diameter of ~ 5nm. As a demonstration of its viability, the Ni2P@BP shows much improved Li storage properties versus the bare BP when evaluated as electrode materials for LIBs.